PERAN KEWIRAUSAHAAN BERBASIS DIGITAL DALAM MENGURANGI TINGKAT PENGANGGURAN - Isra Mirna Noventri; Juli Perawitan Pakpahan; Lia Hutabarat (Universitas Negeri Medan, 2018)
Entrepreneurial creation becomes an alternative solution to various problems in society such as poverty and social inequality, increasing unemployment of productive age and depletion of energy supply reserves, all of which require creative and innovative action. Entrepreneurship is people who are able to turn an opportunity into a business that produces, which is processed through creativity, innovation and uniqueness in making a product and dare to take all possible risks that accompany it and not make it easy to despair if it fails to build the business. It was concluded that entrepreneurship also participated in the development of the State, digital-based entrepreneurship made use of increasingly sophisticated technology, digital-based entrepreneurship as a solution to reduce the unemployment rate, the number of unemployment in indonesia, entrepreneurship is something that must be instilled by the youth and the people of indonesia.